John and Elaine Steinbeck at the Hotel Palais Jamais, Morocco - Unknown:::Creator:::::::::::: (Fes; Morocco, 2022)
John and Elaine Steinbeck on the top terrace at the Hotel Palais Jamais a historic late 19th-century mansion in Fes, Morocco, which was converted to a luxury hotel.